2012
DOI: 10.1590/s0004-27492012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond assisted intrastromal corneal ring (ISCR) implantation for the treatment of corneal ectasia

Abstract: Purpose: To assess the outcomes of intrastromal corneal ring (ISCR) implantation for the treatment of corneal ectasia. Methods: Thirty-five consecutive patients with secondary corneal ectasia treated with keraring intrastromal corneal ring segment implantation aided by intralaser femtosecond technique (K-ICRS-FS) were evaluated. Visual acuity (logMAR), refraction and astigmatism vector analysis were measured preoperatively and 3 months postoperatively using vector analysis as described by some authors. Conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…Similarly, in a 35-eye study, Coimbra et al demonstrated that Keraring ICRS improved visual acuity and topographic data in patients with secondary corneal ectasia at a 3-month postoperative follow-up (11) . However, to the best of our knowledge, no reports on the use of Keraring ICRS as a treatment for patients who have already been triaged for corneal transplantation are available.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, in a 35-eye study, Coimbra et al demonstrated that Keraring ICRS improved visual acuity and topographic data in patients with secondary corneal ectasia at a 3-month postoperative follow-up (11) . However, to the best of our knowledge, no reports on the use of Keraring ICRS as a treatment for patients who have already been triaged for corneal transplantation are available.…”
Section: Discussionmentioning
confidence: 81%
“…There are several commercially available ICRS that vary with regard to curvature, width, and zone of implantation (3) . (10)(11)(12)(13)(14) . Although previous studies have evaluated ICRS efficacy in patients who were intolerant to rigid contact lenses (and therefore potential candidates for a corneal transplant) (15)(16)(17) , to the best of our knowledge, there are no published data regarding Keraring ICRS efficacy in patients with keratoconus who were already scheduled for penetrating keratoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal ring implants were initially used to treat low myopia 4,5, but current applications include treatments for keratoconus, irregular astigmatism induced by penetrating keratoplasty, post-refractive surgery ectasia, post-radial keratotomy ectasia, pellucid marginal degeneration and post-traumatic corneal irregularities 6-8.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have emphasized the advantages of the implants, including their removable nature and their stability and security due to the lack of need for an intraocular procedure 6-11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation